Subjective Cognitive Complaints in Newly-Diagnosed Parkinson’s Disease With and Without Mild Cognitive Impairment - Pan, Chenxi; Ren, Jingru; Hua, Ping; Yan, Lei; Yu, Miao; Wang, Yajie; Zhou, Gaiyan; Zhang, Ronggui; Chen, Jiu; Liu, Weiguo (Frontiers in Neuroscience, 2021)
Background: Subjective cognitive complaints (SCC) and mild cognitive impairment (MCI) are common among patients with Parkinson’s disease (PD). However, the relationship between SCC and MCI is not well understood. Herein, we aimed to investigate whether there are any differences in the prevalence and risk factors of SCC between early PD patients with and without MCI. Methods: Overall, 108 newly diagnosed, untreated PD patients underwent comprehensive neuropsychological assessments. PD patients with mild cognitive impairment (PD-MCI) were diagnosed according to the MCI level II criteria. Furthermore, SCC was measured with the Cognitive Complaints Interview (CCI). Logistic regression analysis, after adjusting for confounding variable, was performed in order to investigate risk factors of SCC in PD-MCI patients and PD patients with normal cognition (PD-NC). Results: Furthermore, 42 (42.3%) participants reported SCC and 53 (53.5%) participants were diagnosed with PD-MCI. The prevalence of SCC in PD-MCI and PD-NC participants was 30.3% and 12.1%, respectively. Logistic regression analyses revealed that the presence of SCC in PD-MCI group was significantly associated with Non-Motor Symptoms Questionnaire (NMSQ) score (OR = 1.340, 95%CI = 1.115-1.610, p = 0.002), while the presence of SCS in PD-NC group was significantly associated with time of Stroop Color-Word Test card C (OR = 1.050, 95%CI = 1.009-1.119, p = 0.016). Conclusion: SCC is frequent among patients with early PD. The prevalence and risk factor of SCC are distinct in PD with and without MCI. These findings suggest that SCC in early PD with different cognition appears to have different pathogenicity.